LINGUISTIC ADAPTATION OF AVIATION TERMINOLOGY IN UZBEK (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the linguistic adaptation of aviation terminology in the Uzbek language. Special attention is given to phonetic, lexical, grammatical, structural, and semantic adaptation processes of aviation terms borrowed mainly from English through direct international communication and technological development. The study analyzes the mechanisms through which foreign aviation terms become integrated into Uzbek linguistic norms and professional discourse. Comparative, descriptive, structural, and semantic analysis methods are employed to identify the main adaptation patterns. The research demonstrates that aviation terminology in Uzbek undergoes systematic phonetic and morphological modifications while preserving technical precision and communicative effectiveness. The article also discusses the role of globalization, international aviation standards, and professional communication in the development of modern Uzbek aviation vocabulary.